EDUCAÇÃO A DISTÂNCIA E FETICHISMO TECNOLÓGICO: Estado e capital no projeto de ensino superior no Brasil - Nascimento, Alberico Francisco do (2011)
Analyze the expansion of the Distance Learning public policies to the undergraduate, specifically to the teachers education, considering the state, the capital and the new technologies ideological action (technological fetishism). The study shows the connection of this scenery with the dominant project of education and points its relation with the new cultural demands imposed by the neo liberalism, highlighting the alienated function of the technical progress ideology. On the other hand, it approaches the objectives of an emancipated education, able to capacity the work class to life. Analyze the categories technological fetishism, ideology and capitalist sociability and argument that the organic relation between the state and capital imposed to the social fellow notions and values about the use of the new technologies that contribute to the enlargement reproduction of the capital. Highlight the state reform, the Mundial Bank documents and the university reform, as elements used to open the way to the consolidation of the neoliberal undergraduate project, in which the Distance Learning is focused as a general solution. In the empiric area, Ratify the mass and mercantile growth of the Distance Learning, when approach its historical evolution up to LDB 9.394/94. Approach the Distance Learning programs implemented by the state to capacity teachers for the Basic Education level, showing its emphasis in the technical professional aspect to the detriment of the epistemological highlight inherent to the teacher s knowledge. Highlight the Brazil Open University (UAB) as an education proposal harmful to the work class that struggles for education at the university. The results of this research showed that the Distance Learning were consolidated through the fetishism technological, that cancel the class character of the technologies and present it only as applied science. From this corroboration, affirm that the actual scenery of the Distance Learning is a state and capital construction to intensify the capitalist offensive in the educational context, through the precarization of the virtual teachers work and over the democratization cloak, massy and mercantile the education at university. The reflections developed in this research aim to change and qualify the teachers to face the internalizations process of the dominant ideology and to struggle for an omnilateral education proposal, beyond the capital.